Primary Tubercular Chorioretinitis Without a Pulmonary Focus: A case of Ocular Tuberculosis - Khalil, Ibrahim (Bangladesh Journal of Medicine, 2024)
Tuberculosis is a global health problem. Around 2 billion people could have TB, with 10.6 million falling ill each year. TB remains deadly despite being preventable and treatable, claiming over 3,500 lives daily and totaling 1.3 million deaths annually. Additionally, approximately 30% of TB cases are missed by healthcare screenings and diagnostics, leading to poor health outcomes and further TB spread in communities. Untreated individuals can infect 10 to 15 others per year, with 10% developing active TB in their lifetimes. TB is an infectious disease that can affect various organs in the body, including the eye. Establishing the diagnosis of ocular TB is a clinical challenge, as most tubercular infections affect the pulmonary system first, and primary infection of the eye is extremely rare, with an incidence of about 1% to 2% .Ocular tuberculosis (TB) can affect various eye structures and may manifest independently of systemic TB. Typically, it arises from hematogenous dissemination from a primary focus; however, in exceptional instances, it may originate as a primary infection after epithelial injury. Diagnosing TB in an extrapulmonary site presents a significant clinical challenge. We present the case of a 25-year-old male who presented with a deteriorating loss of central vision in his right eye. A thorough neurologic examination and serological tests, the tuberculin skin test, a X-ray of the chest, ocular fundus photography, and optical coherence tomography were performed. Based on the clinical features and the outcome of appropriate tests, a presumptive diagnosis of ocular TB was made and later confirmed after initiating antitubercular therapy, which resulted in a marked improvement in the patient’s vision a week later. This case is an illustration of the rare nature and unusual presentation of extrapulmonary TB in the form of tubercular chorioretinitis, diagnosed in a resource-limited setting. Tubercular chorioretinitis, characterized by inflammation of the choroid and retina due to TB infection, presents a diagnostic challenge, especially in resource-limited environments where access to advanced diagnostic tools may be restricted. Therefore, this case highlights the importance of considering TB as a potential cause of ocular manifestations, even in settings where TB prevalence might not be high, and underscores the need for increased awareness and diagnostic capacity for extrapulmonary TB in resource-limited areas. This case exemplifies the infrequent occurrence and atypical manifestation, presenting a learning opportunity for future clinicians. Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 172